KEBIJAKAN PEMBERIAN REMISI DAN PEMBEBASAN BERSYARAT KEPADA NARAPIDANA KASUS NARKOBA DAN KORUPSI DI KABUPATEN KLATEN - Susanto, Eko Bekti (Dinamika Hukum, 2016)
The research aims to: (1) know the implementation of the granting remission and parole for prisoners convicted for drug offense and corruption in Klaten’s prison; (2) know the implication of the granting remission and parole for the prisoners convicted for drug offense and corruption in Klaten’s prison. This research is based on the normative research by using various deduction and induction analysis. It is started by collecting primary data in the form of Government Regulation especially Law No.12 Year 1995 about Correctional System, Government Regulation No. 31 Year 1999 about Terms and Condition of the Exercise of the Prisoner’s Rights and its amendment, and the data about the remission and parole given to the prisoners convicted for drugs and corruption in Klaten’s prison. The result of the research shows that: (1) Before the launch of Government Regulation No. 9 Year 2012, the prisoners convicted for drugs and corruption in Klaten’s prison are still able to receive remission and parole although the conditions to acquire the rights are different between general crime and special crime prisoners (drugs offense and corruption); (2) After the launch of Government Regulation No. 9 Year 2012, the prisoners convicted for drugs and corruption face difficulties to access their rights to receive remission and parole because there are two more additional requirements which are: the willingness to cooperate with the law enforcer to reveal their cases and the large amount of fine they have to pay.Remission and parole are two of the several prisoners’ rights. The difference in treatment for the prisoners convicted for drugs and corruption as the extraordinary crime is needed. However, they should be given a chance to access and receive those rights. Keywords: Corruption, Drugs, Prisoners, Parole, Remission